2010
DOI: 10.1152/jn.00991.2009
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of the Auditory Cortex Impair Azimuthal Sound Localization and Its Recalibration in Ferrets

Abstract: Nodal FR, Kacelnik O, Bajo VM, Bizley JK, Moore DR, King AJ. Lesions of the auditory cortex impair azimuthal sound localization and its recalibration in ferrets. J Neurophysiol 103: 1209 -1225, 2010. First published December 23, 2009 doi:10.1152/jn.00991.2009. The role of auditory cortex in sound localization and its recalibration by experience was explored by measuring the accuracy with which ferrets turned toward and approached the source of broadband sounds in the horizontal plane. In one group, large bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
73
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 36 publications
13
73
0
2
Order By: Relevance
“…The multiple inputs to the auditory cortex, and the multiple pathways through the auditory cortex, are possible reasons why the immediate and temporary nature of cortical inactivation via cooling produces such pronounced behavioral deficits when compared with the rather more nuanced changes observed after more prolonged forms of inactivation or permanent lesions (Heffner, 1997; Smith et al, 2004; Bizley et al, 2007b; Malhotra and Lomber, 2007; Nodal et al, 2010, 2012). These multiple pathways potentially provide the auditory cortex with a basis by which considerable compensatory plasticity can occur, with information organized in a frequency‐specific way still gaining access to the auditory cortex even in the absence of an intact auditory core.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple inputs to the auditory cortex, and the multiple pathways through the auditory cortex, are possible reasons why the immediate and temporary nature of cortical inactivation via cooling produces such pronounced behavioral deficits when compared with the rather more nuanced changes observed after more prolonged forms of inactivation or permanent lesions (Heffner, 1997; Smith et al, 2004; Bizley et al, 2007b; Malhotra and Lomber, 2007; Nodal et al, 2010, 2012). These multiple pathways potentially provide the auditory cortex with a basis by which considerable compensatory plasticity can occur, with information organized in a frequency‐specific way still gaining access to the auditory cortex even in the absence of an intact auditory core.…”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated in animal models following monaural plugging (King et al, 2000; Kacelnik et al, 2006; Irving et al, 2011), deactivation of areas of auditory cortex (Nodal et al, 2012) and lesions to auditory cortex (Nodal et al, 2010). In humans, artificially altering the pinnae or other ear structures (e.g., occluding the concha with a custom earmold), deteriorates localization accuracy (Wightman and Kistler, 1997; Hofman et al, 1998; Van Wanrooij and Van Opstal, 2004; Irving and Moore, 2011; Agterberg et al, 2012).…”
Section: 1 Introductionmentioning
confidence: 90%
“…Sound localization deficits can last for months, depending on when, during postnatal development, the ear canal is blocked (Knudsen et al 1984b). More recent investigations in ferret have shown that intensive perceptual training can restore localization accuracy following unilateral auditory deprivation and that this plasticity relies critically on the function of descending corticocollicullar connections, highlighting the potential importance of auditory cortex circuits in the expression of amblyaudia (Kacelnik et al 2006;Bajo et al 2010;Nodal et al 2010). …”
Section: Basic Research Studies Linking Developmental Auditory Deprivmentioning
confidence: 99%